2014
DOI: 10.1159/000365652
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastography Maximal Clot Strength Could Predict One-Year Functional Outcome in Patients with Ischemic Stroke

Abstract: Background: Elevated maximal clot strength, measured by thrombelastography (TEG) maximum amplitude (MA) has been associated with a higher risk for ischemic events in patients with coronary artery diseases. However, it has not been investigated in patients with cerebrovascular diseases. In the current study, we aimed to evaluate the predictive ability of TEG-MA in assessing the risk for ischemic event recurrence and the functional outcome after index ischemic stroke. Methods: This was a prospective observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…By comparison, patients with END corresponded to a higher proportion of females (45.8 vs. 18.4%, p < 0.001), higher rates of DM history (38.9 vs. 20.1%, p = 0.015), higher baseline NIHSS score (5 [3][4][5][6][7][8][9] vs. 2 [1][2][3][4], p = 0.001), and higher serum high-sensitivity C-reactive protein (hsCRP) levels (5.60 [2.46-7.14] vs. 1.65 [0.70-4.68], p = 0.002). In the comparison of TEG parameters, patients in the END group had a significantly shorter reaction time R (4.0 ± 1.0 vs. 4.7 ± 1.2 min, p < 0.001) and kinetic time K (1.3 ± 0.4 vs. 1.5 ± 0.4 min, p = 0.003) than patients without END.…”
Section: Demographic and Baseline Characteristicsmentioning
confidence: 93%
See 1 more Smart Citation
“…By comparison, patients with END corresponded to a higher proportion of females (45.8 vs. 18.4%, p < 0.001), higher rates of DM history (38.9 vs. 20.1%, p = 0.015), higher baseline NIHSS score (5 [3][4][5][6][7][8][9] vs. 2 [1][2][3][4], p = 0.001), and higher serum high-sensitivity C-reactive protein (hsCRP) levels (5.60 [2.46-7.14] vs. 1.65 [0.70-4.68], p = 0.002). In the comparison of TEG parameters, patients in the END group had a significantly shorter reaction time R (4.0 ± 1.0 vs. 4.7 ± 1.2 min, p < 0.001) and kinetic time K (1.3 ± 0.4 vs. 1.5 ± 0.4 min, p = 0.003) than patients without END.…”
Section: Demographic and Baseline Characteristicsmentioning
confidence: 93%
“…Currently, there is great interest in the clinical applications of thromboelastography (TEG), which can provide an integrated view of the viscoelasticity and coagulability properties of blood. Some studies have suggested that TEG is a useful tool for predicting stroke recurrence in patients with cardiovascular diseases [9,10]. However, few studies have assessed whether and to what degree TEG findings are associated with ischemic tissue evolution in patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al recently described the use of TEG in AIS patients. They obtained a TEG on a cohort of 211 patients with AIS and found that hypercoagulability on TEG (defined on this cohort as an MA of C69 mm) was found to be an independent predictor of an unfavorable outcome at 1 year [31].…”
Section: Acute Ischemic Stroke (Ais)mentioning
confidence: 99%
“…Разнородность данных не позволи-ла провести метаанализ. Несколько более поздних работ подтверждают предсказательную силу параметра максимальной амплитуды (МА): МА либо G (жест-кость сгустка = 5,000 MA / 100 -MA) у пациентов по-сле операций является независимым фактором риска повторного ишемического инсульта (ОШ 1,192; p = 0,022) [49], а также других тромботических осложне-ний, в том числе инфаркта миокарда [50,51]. Подоб-ные данные имеются для аналога ТЭГ -ROTEM [47].…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified
“…Подоб-ные данные имеются для аналога ТЭГ -ROTEM [47]. Параметр МА в основном определяется функцией тромбоцитов и концентрацией фибриногена [52], что объясняет отсутствие корреляции МА с АЧТВ и МНО [49].…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified